2013
DOI: 10.1111/jnc.12122
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase C‐η2 is required for retinoic acid‐stimulated neurite growth

Abstract: Phospholipase C-g2 is a recently identified phospholipase C (PLC) implicated in the regulation of neuronal differentiation/ maturation. PLCg2 activity is triggered by intracellular calcium mobilization and likely serves to amplify Ca 2+ signals by stimulating further Ca 2+ release from Ins(1,4,5)P 3 -sensitive stores. The role of PLCg2 in neuritogenesis was assessed during retinoic acid (RA)-induced Neuro2A cell differentiation. PLCg2 expression increased two-fold during a 4-day differentiation period. Stable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…In accordance, deletion of the chromosomal region 1p36.32 in which PLCη2 is located, leads to mental retardation (Fitzgibbon et al 2008 ; Lo Vasco 2011 ). Previously, using a targeted knockdown approach, we found PLCη2 to be essential for retinoic acid-induced neurite growth in Neuro2A cells (Popovics et al 2013 ). Despite this, the precise mechanism by which PLCη2 facilitates neurite growth in these cells is not known.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance, deletion of the chromosomal region 1p36.32 in which PLCη2 is located, leads to mental retardation (Fitzgibbon et al 2008 ; Lo Vasco 2011 ). Previously, using a targeted knockdown approach, we found PLCη2 to be essential for retinoic acid-induced neurite growth in Neuro2A cells (Popovics et al 2013 ). Despite this, the precise mechanism by which PLCη2 facilitates neurite growth in these cells is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, the precise mechanism by which PLCη2 facilitates neurite growth in these cells is not known. In our previous study, through use of a bacterial two-hybrid assay we identified Lim-domain kinase-1 (LIMK-1) as a putative C-terminal interaction partner of PLCη2 (Popovics et al 2013 ). LIMK-1 acts primarily downstream of Rho GTPases to phosphorylate and inactivate cofilin family proteins (cofilin1, cofilin2 and destrin), which promote actin depolymerization and the severing of actin filaments during neurite outgrowth (Arber et al 1998 ; Yang et al 1998 ; Endo et al 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…6 , A and B ). Because PLCη2 was reported to localize to the plasma membrane by binding to PI(4,5)P 2 via its PH domain ( 41 , 48 ), the observed filamentous distribution of EGFP-PLCη2 ( Fig. 6 A ) could result from binding to PI(4,5)P 2 -rich membrane domains that co-localize along F-actin filaments.…”
Section: Resultsmentioning
confidence: 99%
“…Both catalyze hydrolysis of PIP 2 (Nakahara et al, 2005;Hwang et al, 2005;Zhou et al, 2005), which suggests that these enzymes, like other PIP 2 -specific PLCs, are involved in the production of DAG and IP 3 . The cellular function of these enzymes is not entirely clear, although a recent study highlighted a potential role for PLCη2 in regulating neurite growth (Popovics et al, 2013). It has become apparent that both PLCη enzymes are activated by intracellular Ca 2+ mobilization (Kim et al, 2011;Popovics et al, 2011), and are sensitive to changes in [Ca 2+ ] i within the physiological range (Nakahara et al, 2005;Hwang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%